Duodenogastric reflux: a cause of gastric mucosal hyperaemia and symptoms after operations for peptic ulceration. Issue 1 (January 1975) - Keighley, M R; Asquith, P; Alexander-Williams, J
Abstract : This study has investigated the possible association between duodenogastric reflux, gastritis, and symptoms in 35 patients with or without dyspepsia one to 15 years after gastric surgery. Five patients were excluded because of biliary disease, hiatus hernia, or recurrent ulceration. The remaining 30 were assessed by a symptomatic score, measurement, of bilirubin and sodium concentrations in samples of fasting gastric juice, endoscopy, gastric biopsy, and the presence of radiological reflux. In 15 patients with a symptom score of less than the median, gastric bilirubin levels were less than 1 mg/100 ml in 80%; severe endoscopic changes were seen in only one patient and reflux was not observed. In contrast, in patients with a symptom score in excess of the median fluoroscopic and biochemical reflux was seen in 69 and 80% respectively and severe mucosal hyperaemia in half. There was a significant correlation between symptoms, gastric hyperaemia, and duodenal reflus ( P smaller than 0-02).